Existence and Controllability Results for Higher Order Caputo Fractional Damping System with Impulses - Tamilarasi, M.; Radhakrishnan, B. (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates the presence of mild solutions and controllability for higher order Caputo fractional damped differential systems with impulses. The general method of Laplace transform, Grammian matrix, and sequential approximation techniques are used to establish the controllability requirement for the linear and nonlinear fractional damped dynamical systems of higher order. At the end, an example is provided to validate the theoretical results.